Impact of Glycine Supplementation on Growth and Hematological Indices in Florida Pompano (Trachinotus carolinus) - Trinh H. V. Ngo; Marty Riche; Timothy J. Bruce; Luke A. Roy; D. Allen Davis (Aquaculture Nutrition, 2025)
With the rising incorporation of alternative protein sources in fish diets, understanding amino acid (AA) supplementation strategies, including glycine, optimizes fish growth performance and immune function. A 12-week feeding trial evaluated the effect of dietary glycine (Gly) supplementation on the growth performance and blood biochemistry of juvenile Florida pompano (Trachinotus carolinus; 19.55 ± 0.32 g). Experimental diets incorporated soybean meal (SBM), poultry by-product meal (PBM), and corn protein concentrate, and were formulated to contain 40% crude protein and 8% crude lipid. Glycine was supplemented at 0%, 0.25%, 0.5%, and 1%, with alanine (Ala) adjustments to ensure all diets were isonitrogenous. Growth metrics, including final weight (FW) (85.21–90.93 g), weight gain (WG) (336%–366%), and feed conversion ratio (FCR) (1.61–1.69), showed no significant differences among treatments. A significant linear decrease in the hepatosomatic index (R2 = 0.244, p=0.027), stable liver enzymes, and a significant increase in serum cholesterol at 1% glycine supplementation (R2 = 0.507; p=0.002) suggest that glycine may influence hepatic metabolism, potentially through enhanced bile acid conjugation. Whole-body proximate composition and AA profiles remained unchanged, and serum lysozyme activity (SLA) showed no significant variation across treatments (p=0.730). These findings suggest that glycine supplementation did not enhance growth but influenced some metabolic parameters. Further research is suggested to clarify the underlying mechanisms under various cultural conditions and stress challenges.